Исследование вероятостных сценариев алгебраических атак на потоковые шифры - Пометун, С.А. (Проблемы управления и информатики, 2009)
Суть алгебраїчних атак на потокові шифри полягає у пониженні степеня системи рівнянь, які пов’язують біти невідомого ключа з відомими вихідними бітами шифру. Імовірнісні сценарії атаки дають ще більше пониження степеня, але отримані рівняння істинні вже не на всіх аргументах. Ці сценарії досліджено, а також введено відповідні поняття, за допомогою яких описується стійкість ускладнюючої булевої функції потокового шифру проти таких атак. The essence of algebraic attacks on stream ciphers lies in lowering, in a definite way, of degree of equations, relating the bits of an unknown key to known output cipher bits. Probabilistic scenarios of an attack presuppose even greater reduction of degree, but in this case the received equations are true not with all arguments. In this work such scenarios are investigated. Also corresponding notions were introduced, in terms of which it is easy to describe vulnerability of complicating Boolean function of a stream cipher against such kind of attacks.